An iOS developer's guide to SwiftUI design and build beautiful apps quickly and easily with minimum code - Fadda, Michele (Packt Publishing Limited, 2024)
Get started with SwiftUI and accelerate your iOS app development with this guide to leveraging the declarative approach, with key images printed in color Key Features Learn how to structure and maintain clean app architecture Integrate SwiftUI with relevant frameworks to create professional and responsive apps Understand the declarative functional approach and focus on asynchronous programming within the context of SwiftUI Purchase of the print or Kindle book includes a free PDF eBook Book Description SwiftUI has transformed app development across Apple Platforms, offering developers the power to build seamless user interfaces by just defining the UI design through intuitive Swift code. This book explores SwiftUI's revolutionary declarative programming approach to assist you in designing UI for Apple devices, ranging from iPhones to Macs, by declaring what the app should look like and what it should do, leaving the heavy lifting to the operating system.
Keywords: iOS (Electronic resource); Swift (Computer program language); Application software; Swift (Langage de programmation); Logiciels d'application